142k views
5 votes
-12(a-2)=-50 help help help

User Chrisk
by
7.6k points

2 Answers

4 votes

Answer:

a =
(37)/(6)

Explanation:

-12(a - 2) = -50

-12a + 24 = -50

-12a = -74

a =
(74)/(12) =
(37)/(6)

User BurningLights
by
6.9k points
1 vote

Answer:

a = 37/6

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Explanation:

Step 1: Define equation

-12(a - 2) = -50

Step 2: Solve for a

  1. Divide -12 on both sides: a - 2 = 25/6
  2. Add 2 on both sides: a = 37/6

Step 3: Check

Plug in a into the original equation to verify it's a solution.

  1. Substitute in a: -12(37/6 - 2) = -50
  2. Subtract: -12(25/6) = -50
  3. Multiply: -50 = -50

Here we see that -50 does indeed equal -50.

∴ a = 37/6 is a solution of the equation.

User Woens
by
8.1k points